Comparing two different techniques to repair pediatric anterior tympanic membrane perforations. (November 2021) - Dunya, Gabriel; Casazza, Geoffrey C.; Blotter, Josh; Park, Erica J.; Park, Albert H.
Abstract: Objective: Compare outcomes between a microscopic and endoscopic technique for anterior tympanic membrane (TM) perforation. Methods: Results of microscopic overlay (MT) and endoscopic tympanoplasty (ET) for management of anterior TM perforations from a single surgeon. Results: There were 28 patients in the MT group and 35 in the ET group. The mean age was 7.1 years and 10.9 years (p < 0.001) MT and ET groups respectively. There was no statistical differences in perforation location (p = 0.1), etiology (p = 0.52) or size (p = 0.1) between both groups. Mean operating time was 119.0 min and 131.0 min in the MT and ET groups respectively (p = 0.23). Follow up was 30.9 months and 9.0 months (p = 0.001) MT and ET respectively. The perforation was successfully closed in 29 patients at 6 weeks in the ET (82.9%) and 25 in the MT (89.3%), p = 0.47. Adjusting for age revealed no significant difference between groups. Long term follow up, resulted in 10 failures (28.6%) and 7 patients (25.0%) in the ET and MT groups respectively, p = 0.75. Adjusting for the follow-up period or age, there was no significant difference between groups. The change in ABG and PTA measures were not statistically different between groups. Conclusions: An anteriorly based ET is a novel technique for management of anterior TM perforations. Results from this pilot study indicate that this ET approach may be an appropriate alternative to MT for difficult to repair anterior perforations. A longer follow-up will be necessary to determine its role in these perforations.